Design and Experimental Analysis of Micropolarization Array Based on a Long-Wave Infrared Optical System - Qiang Fu; Yue Zhang; Yi Liu; Haodong Shi; Su Zhang; Juntong Zhan; Yingchao Li; Huilin Jiang (Applied Sciences, 2022)
Aiming at the shortcomings of the traditional infrared polarization imaging device, such as large volume, complex structure, difficult registration, and inability to recognize moving targets, this paper proposes an infrared polarization imaging method based on a micropolarizer. The long refractive wave infrared polarization optical system is designed to achieve the imaging detection of a 0.25 m target at 1 km; for this, a design of a micropolarizer array suitable for the long-wave infrared band is proposed. In the simulation analysis, the effects of the grating substrate and line grating material, grating period, duty cycle, and grating slot depth on the polarization performance of grating are discussed, respectively. Through infrared polarization imaging experiments on typical targets, the unique advantages of infrared polarization technology in distinguishing metal and non-metal, natural and artificial objects, and high-temperature object recognition are verified, which provides practical support for physical evidence searches and camouflage target recognition.